Pengaruh Likuiditas, Leverage dan Aktivitas terhadap Kondisi Financial Distress yang Dimoderasi oleh Profitabilitas: Studi pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2015-2019 - Anita Permata Sari; Ferikawita M. Sembiring (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: The aimed of this study was to found liquidity, leverage, and activity effect to financial distress moderated by profitability in mining companies listed on the IDX in the period 2015-2019, measured by the altman z-score model. Research methodology: Descriptive and associative methods are used as research methods. Sample of this study was 10 mining companies registered in the IDX in the period 2015-2019 obtained by purposive sampling method. The tool used is EViews 10 with panel data regression analysis techniques. Results: The results indicates that only liquidity and leverage had an effect on financial distress. Simultaneusly liquidity, leverage and activity also affect financial distress. Then, profitability is found to moderate the effect of liquidity on financial distress. Limitations: The limitations of the study are on the sample size and the period of research that allows to be added to future research, as well as the possible use of other financial distress measurement methods. Contribution: Produce findings on variables that can affect financial distress in mining companies by using profitability as a moderation variable.